Finite Element Analysis of J-Integral for Surface Cracks in Round Bars under Combined Mode I Loading - Ismail, Al Emran; Ariffin, Ahmad Kamal; Abdullah, Shahrum; Ghazali, Mariyam Jameelah (International Journal of Integrated Engineering, 2017)
This paper numerically discusses the role of J-integral along the surface crack front in cylindrical bar under combined mode I loading. It is also verified the analytical model derived from the first part of this paper by comparing the results obtained numerically using ANSYS finite element program. It is found that the proposed model capable to predict the J-integral successfully along the crack front but not for the area away from the deepest crack depth. This is probably due to the fact that the problem of singularity.